Coping with a Qur'anic Truth Claim. Issue 1 (15th July 2022) - Ellethy, Yaser
Abstract : Since the latter half of the twentieth century, Western philosophers of religion and scholars of religion have been fervently preoccupied with the question of religious truth claims and how to evaluate a Christian theological view of other religious traditions. This resulted in the standardization of inclusivism, exclusivism, and pluralism as distinct universal approaches to the truth claim predicament. Employing Qur'anic exegesis, hermeneutics, and the semantics of core Islamic concepts, this article offers a critique of this standardized typology as less relevant to the Muslim perspective of religious diversity. Based on an Islamic view of the relativity of human knowledge and the centrality of a revelatory epistemic premise, this typology is hardly akin to a Muslim traditional perspective. The Qur'an defines the boundaries between the Islamic truth claim, salvific exclusion, and the ethical codes for Muslims to deal with a worldly context that is ab initio diverse. This article argues that an Islamic pluralistic view, as delineated on the basis of the Qur'an, supersedes the dilemma of religious truth claims and seeks realistic ethical regulations to deal with religious otherness.